2018
DOI: 10.1111/epi.13999
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular allopregnanolone and ganaxolone in a mouse model of treatment‐resistant status epilepticus

Abstract: Allopregnanolone (5α-pregnan-3α-ol-20-one) and its synthetic 3β-methyl analog, ganaxolone, are positive allosteric modulators of synaptic and extrasynaptic γ-aminobutyric acid (GABA) receptors that exhibit antiseizure activity in diverse animal seizure models, including models of status epilepticus (SE). The 2 neuroactive steroids are being investigated as treatments for SE, including as a treatment for SE induced by chemical threat agents. Intramuscular injection is the preferred route of administration in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…Given that GABAergic neuroactive steroids have potent anticonvulsant effects in several animal models (Devaud et al, ; Reddy and Rogawski, ), and potent modulatory actions at extrasynaptic GABA A receptors (Belelli and Lambert, ), they may be valuable therapeutic agents. Indeed, allopregnanolone and its synthetic 3β‐methyl analog ganaxolone both proved effective in rodent (mostly males) models of treatment‐resistant status epilepticus (Rogawski et al, ; Zolkowska et al, ). Furthermore, case reports, limited to 2 young girls and 2 young adult men, suggested that intravenous allopregnanolone may be therapeutic for status epilepticus in a number of individuals (Broomall et al, ; Vaitkevicius et al, ).…”
Section: Alcohol Addiction Results From Loss Of Gabaa Receptor‐mediatmentioning
confidence: 99%
“…Given that GABAergic neuroactive steroids have potent anticonvulsant effects in several animal models (Devaud et al, ; Reddy and Rogawski, ), and potent modulatory actions at extrasynaptic GABA A receptors (Belelli and Lambert, ), they may be valuable therapeutic agents. Indeed, allopregnanolone and its synthetic 3β‐methyl analog ganaxolone both proved effective in rodent (mostly males) models of treatment‐resistant status epilepticus (Rogawski et al, ; Zolkowska et al, ). Furthermore, case reports, limited to 2 young girls and 2 young adult men, suggested that intravenous allopregnanolone may be therapeutic for status epilepticus in a number of individuals (Broomall et al, ; Vaitkevicius et al, ).…”
Section: Alcohol Addiction Results From Loss Of Gabaa Receptor‐mediatmentioning
confidence: 99%
“…Improvements in PK characteristics were extended to improvements in duration of antiseizure activity, with a 2-to 4-fold longer duration of action than that of ALLO. Note that in a recent report ALLO was found to produce a faster onset of action and a better antiepileptic response than GNX in a mouse model of SE (Zolkowska et al, 2018). However, this study was conducted with i.m.…”
Section: Time Of Administrationmentioning
confidence: 95%
“…For the long-term PK study, we utilized the so-called "TETS SE model", in which adult male NIH-NCI Swiss mice are pretreated with riluzole 10 min prior to TETS administration (Zolkowska et al 2018). Riluzole was prepared in 10% Captisol® (Ligand Technology, La Jolla, CA) and 90% saline at 10 mg/mL and further diluted 1:10 in sterile saline for i.p.…”
Section: Tets Pharmacokineticsmentioning
confidence: 99%
“…To our surprise, we observed that TETS serum concentrations basically "flat-lined" at ~ 600 nM in blood samples taken at 1 min, 5 min, 10 min, 20 min, 40 min, 60 min instead of decreasing with the normally observed mono-or biexponential decay. To further investigate this persistence, we next designed a long-term PK experiment in the "TETS SE model", in which adult male NIH-NCI Swiss mice are pretreated with riluzole 10 min prior to TETS administration (Zolkowska et al 2018). The riluzole pretreatment prevents mice from succumbing to tonic hindlimb extension, and thus the majority of animals go into a prolonged status epilepticus following i.p.…”
Section: Tets Is Metabolically Stable and Persists In Vivomentioning
confidence: 99%